Synergizing Financial Management and Regional Development Planning: Case Study of Homestay-Based Tourism Villages in Deli Serdang, North Sumatra Indonesia - Dina Rosari (PT. Anagata Sembagi Education, 2025)
This study examines the influence of regional development planning and financial management on the sustainability of homestay-based tourism villages, community empowerment, and service quality & economic performance, with synergy/integration serving as a mediating variable. Using a quantitative approach and the SEM-PLS method, data were collected from 101 homestay managers and tourism village stakeholders. The results reveal that both regional development planning and financial management have significant positive effects on synergy/integration among stakeholders. Furthermore, synergy/integration strongly enhances the sustainability of tourism villages, empowers the local community, and improves service quality and economic outcomes. Mediation analysis confirms that the positive impacts of planning and financial management on key outcomes are primarily realized through synergy/integration. These findings highlight the critical role of stakeholder collaboration and integration in achieving sustainable, empowering, and high-performing tourism villages. The study offers practical recommendations for strengthening collaboration, capacity building, and policy development to support the long-term success of homestay-based tourism villages.